Financial and infrastructure centers of the Western region of Ukraine - Lohin, Zlata (Human Geography Journal, 2022)
The article analyses the financial and infrastructural hubs, centres and points that are the point forms of geospatial organization of the financial infrastructure of the Western region of Ukraine. The definition of the concepts "financial and infrastructural hub", "financial and infrastructural centre" and "financial and infrastructural point" is offered. Specific point forms of geospatial organization at three levels are considered. A feature of the financial infrastructure is its ability to make rapid changes that can be caused at the local, regional, national and global levels, so its transformation occurs simultaneously through two multifunctional processes – globalization and regionalization.There are four main provisions that are provided by the geospatial organization, namely: a) the relative location of objects; b) the existence of relationships of different types (spatial information, human, etc.); c) the existence of territorial social formations (structures, entities, systems); d) their ability to continue to operate (availability of conditions for transformation). The influence of demographic and socio-economic factors was revealed on the selection of specific point forms of financial infrastructure, the social potential of settlements in the study region was taken into account. Particular attention is paid to financial and infrastructure centres, as more requirements are placed on their allocation. Financial and infrastructural centers are also formed under the influence of historical and geographical factors. Attention is drawn to the problem of transforming specific point-type objects from point to centre to hub and vice versa. The impact of decentralization reform and the new administrative-territorial structure, which led to an increase in the number of financial and infrastructural points but reduced the number of financial and infrastructural centres, are taken into account.